Phenolic profile by HPLC-ESI-MS/MS of six Brazilian Eugenia species and their potential as cholinesterase inhibitors. Issue 15 (3rd August 2021) - Tenfen, Adrielli; Vechi, Giovana; Cechinel-Zanchett, Camile Cecconi; Lorenzett, Thaís Savoldi; Reginato-Couto, Camila Esmério; Siebert, Diogo Alexandre; Vitali, Luciano; Micke, Gustavo; Klein-Júnior, Luiz Carlos; Cechinel Filho, Valdir
Abstract: Eugenia genus is known for its phenolic metabolites, which may influence the progression of the Alzheimer Disease. This study aimed to evaluate the anticholinesterase effects of six Eugenia species from Brazil. Leaves and stems were submitted to maceration (methanol) and partitioned with dichloromethane and ethyl acetate (EtOAc). Samples were screened (200 μg mL −1 ) for the inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). HPLC-ESI-MS/MS analysis allowed the identification of twenty-eight phenolic compounds. Regarding the enzymatic activity, EtOAc fraction of E. mattosii exhibited the best results. Chemical and pharmacological aspects of seasonal E. mattosii extracts were evaluated. The extract from leaves collected in the winter was the most effective for AChE, and the extract from leaves collected in the spring was the most effective for BuChE. Correlating the enzymatic results with the chemical data, it was possible to associate these effects to isoquercitrin, quercetin, catechin, epicatechin, procatecuic acid and myricitrin content. Abstract : UF0001